18FDG-PET to assess recurrence and long term survival in patients with malignant melanoma - Wieder, H. A.; Tekin, G.; Rosenbaum-Krumme, S.; Klode, J.; Altenbernd, J.; Bockisch, A.; Nagarajah, J. (Nuklearmedizin - NuclearMedicine, 2013)
Aim: To assess the diagnostic and prognostic value of FDG-PET/CT in the follow-up of malignant melanoma in comparison to the serum protein S100B. Patients and methods: A total of ninety patients with either low-risk or high-risk malignant melanoma, respectively, were included in this study. The followup of the patients was pursuant with the guidelines of the German Dermatological Association. The diagnostic accuracy and diagnostic power were determined for PET/CT and for the serum protein S100B. Results: In 28 of the 90 patients PET/CT was positive in the follow up, 47 patients had an elevated Serum S100B level. Sensitivity, specificity, PPV and NPV of PET/CT for the total groups of patients were 87%, 93%, 87% and 93%. The corresponding values for the serum protein S100B were 65%, 52%, 43% and 74%, respectively. PET/CT positive patients showed a significantly (p < 0.001) higher risk of melanoma associated death compared to patients with PET/CT negative findings. No statistical significance could be found in the 5 year survival rate between the S100B positive and S100B negative patients. Conclusion: PET/CT is suitable to confirm or exclude recurrences and can be used to assess the prognosis in melanoma patients. The diagnostic accuracy and the prognostic power is much higher compared to the serum protein S100B.
Keywords: PET/CT; recurrence; survival; malignant melanoma